2020
DOI: 10.4103/jfmpc.jfmpc_306_20
|View full text |Cite
|
Sign up to set email alerts
|

A hospital-based cross-sectional study on suicidal poisoning in Western Uttar Pradesh

Abstract: Background and Aims: Poisoning is most common method of committing suicide in India. Objectives of this study to assess prevalence of suicidal poisoning among all poisoning cases, its socio-demographic profile and its reasons in all admitted cases of suicidal poisoning in hospital. Methods: A cross-sectional study was conducted on cases of poisoning of any age group admitted in the Chhatrapati Shivaji Subharti Hospital, Meerut. Poisoning cases with history or evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…24 Studies highlight the prevalence of herbicides, insecticides, and rat poison among suicide attempters, particularly in rural agricultural areas. 18,22,25 In our study, herbicides (52%) were the agents most commonly used, followed by insecticides (24%), and rat poison (9%). Other agents used were fungicides (4%), petroleum (3%), bleaching powder (2%), gammaxene (1%), household disinfectants (1%), unknown poison (3%) and drug overdose (2%).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…24 Studies highlight the prevalence of herbicides, insecticides, and rat poison among suicide attempters, particularly in rural agricultural areas. 18,22,25 In our study, herbicides (52%) were the agents most commonly used, followed by insecticides (24%), and rat poison (9%). Other agents used were fungicides (4%), petroleum (3%), bleaching powder (2%), gammaxene (1%), household disinfectants (1%), unknown poison (3%) and drug overdose (2%).…”
Section: Discussionmentioning
confidence: 59%
“…Research identified a myriad of psychosocial stressors contributing to suicidal ideation, including familial conflicts, marital discord, financial difficulties, and unemployment. 18,22,28 These findings underscore the complex interplay between individual vulnerabilities and external stressors in shaping suicidal behaviour. The stigma surrounding mental health issues and limited access to mental health services may exacerbate the risk of suicide among vulnerable populations.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This can be attributed to increased work stress, family issues, financial strain, and other life-settling issues in this age group. In a study by Patel et al ,[ 16 ] 59.2% of patients with poisoning were male. Similarly, in our study of 236 participants, 143 (60.5%) were males.…”
Section: Discussionmentioning
confidence: 99%